Agama Dalam Pluralitas Budaya - Faisol Rizal (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2019)
Religion, at least, consists of five dimensions: ritual, mystical, ideological, intellectual and social. The ritual dimension is related to religious ceremonies, some rites that are considered sacred such as prayer, mass or worship. The mystical dimension shows religious experience which includes at least three aspects: attention, cognitive systems, beliefs and fear. The ideological dimension refers to a series of beliefs that explain the existence of humans dealing with God and other creatures. The intellectual dimension shows the level of understanding of people towards their religious doctrine. The social dimension is the manifestation of religious teachings in social life. As for the other hand, culture is a complex whole, social heritage or tradition, ways, rules and ways of human life, human adjustments to the natural surroundings and ways to solve problems, the results of human intelligence and the results of association or human association. The methods used in this article is a qualitative approach to the library, where the focus is aimed against any reference about the religion, culture and islamic boarding school. The approach used is qualitative, which is a research procedure that describes the behavior of certain people, events, or places in detail and depth. While this type of research is literature. Namely, research that relies on reading sources, texts, and various information in the form of reading. In a different reference library research is research that is done to solve a problem that is based on a critical study of library materials and related research results presented in new ways.